Theoretical model and computacional procedure to evaluate the NSM FRP strips shear strength contribution to a RC beam - Bianco, V. (2011)
This paper presents a closed-form procedure to evaluate the shear strength contribution provided to a Reinforced Concrete (RC) beam by a system of Near Surface Mounted (NSM) Fiber Reinforced Polymer (FRP) strips. This procedure is based on the evaluation of: a) the constitutive law of the average-available-bond-length NSM FRP strip effectively crossing the shear crack and b) the maximum effective capacity it can attain during the loading process of the strengthened beam. Due to complex phenomena, such as: a) interaction between forces transferred through bond to the surrounding concrete and the concrete fracture, and b) interaction among adjacent strips, the NSM FRP strip constitutive law is largely different than the linear elastic one characterizing the FRP behavior in tension. Once the constitutive law of the average-available-bond-length NSM strip is reliably known, its maximum effective capacity can be determined by imposing a coherent kinematic mechanism. The self-contained and ready-to-implement set of analytical equations and logical operations is presented along with the main underlying physical-mechanical principles and assumptions. The formulation proposed is appraised against some of the most recent experimental results, and its predictions are also compared with those obtained by a recently developed more sophisticated model.